(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Coal still ranks the second largest source of total global energy demand, which is complementedby the high-risk nature of coal mining activity. Therefore, it is important to discuss the health issues of coalworkers. One of the risks associated with coal mining activities is poor indoor air quality (IAQ) due to thehigh concentration of airborne pollutants. Methods: This study aims to evaluate the results of air qualitymeasurements in the PT X office, and the method used was a descriptive approach with quantitative secondarydata. Furthermore, the measured variables are NO2, SO2, CO2, CO, Pb, PM10, temperature, humidity, andnoise. Conclusion: The results showed that there was an IAQ problem, namely noise, temperature, andhumidity which exceed the recommendations. Therefore, the IAQ management implemented by PT X wasstill systematically and comprehensively developing.